(untitled) (Ameghiniana, 2014)
Quetecsaurus rusconii gen. et sp. nov. is a new titanosaur (Dinosauria, Sauropoda) from the Neuquén Basin of Mendoza Province, Argentina. The specimen comes from red mudstones of the Cerro Lisandro Formation (middle-late Turonian, Upper Cretaceous), and is the first sauropod with well-preserved remains to be discovered in this formation. The holotype includes a postorbital, teeth, the atlas, a poste- rior cervical vertebra, an incomplete dorsal vertebra, a posterior caudal centrum, dorsal ribs, a coracoid, fragments of a humerus, radius and ulna, and five metacarpals. It is characterized by the following combination of autapomorphies: (1) intercentrum of atlas with a prominent anteroventral border and expanded posteroventral processes; (2) posterior cervical neural spines with incipient lateral expansions; and (3) humerus with strongly sigmoid proximal border, rounded proximomedial border, and angular proximolateral corner. A preliminary cladis- tic analysis placed Quetecsaurus as a sister taxon of Lognkosauria (Mendozasaurus + Futalognkosaurus). Quetecsaurus shares with the lognkosaurs the presence of cervical neural spines with ‘lateral laminae’, but relatively reduced in comparison with those taxa. This discovery provides new information on the diagnosis of Lognkosauria within South American titanosaurs.